1989
DOI: 10.1111/j.1476-5381.1989.tb11977.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of acetylcholinesterase and butyrylcholinesterase from the guinea‐pig isolated ileum

Abstract: Strips of longitudinal muscle from guinea‐pig ileum, retaining Auerbach's plexus, were superfused with oxygenated Krebs solution. Addition of 50 mm KCl led to a pronounced Ca2+‐dependent increase in the activities of both acetylcholinesterase and non‐specific cholinesterase (butyrylcholinesterase) in the perfusate but with no change in lactate dehydrogenase activity. No release of acetylcholinesterase, either spontaneous or K+‐evoked was observed in tissue freed of the nerve plexus, although release of butyryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…They claim that neurotransmitter hydrolysis may be controlled via two enzymatic pathways: the primary system is acetylcholinesterase for the acetylcholine, which is held in the synaptic cleft and the secondary system, using plasma cholinesterase, for the extraneuronal acetylcholine which has diffused into the smooth muscle regions. This physiological finding agrees with the anatomical findings of Appleyard & Smith [13] who found that the acetylcholinesterase was present in Auerbach's plexus of a guinea-pig's ileum whereas the plasma cholinesterase was detected mainly in the smooth muscle.…”
Section: Physiology Of the Cholinesterasessupporting
confidence: 92%
“…They claim that neurotransmitter hydrolysis may be controlled via two enzymatic pathways: the primary system is acetylcholinesterase for the acetylcholine, which is held in the synaptic cleft and the secondary system, using plasma cholinesterase, for the extraneuronal acetylcholine which has diffused into the smooth muscle regions. This physiological finding agrees with the anatomical findings of Appleyard & Smith [13] who found that the acetylcholinesterase was present in Auerbach's plexus of a guinea-pig's ileum whereas the plasma cholinesterase was detected mainly in the smooth muscle.…”
Section: Physiology Of the Cholinesterasessupporting
confidence: 92%
“…AChE inhibitors decrease metabolism of ACh released from enteric neurons. 26 Blocking metabolism of ACh increases the availability of ACh and probably the effective distance over which ACh can diffuse from excitatory nerve terminals to affect postjunctional receptors. A result of preserving ACh in the tunica muscularis should be enhanced binding of muscarinic receptors that exert ionotropic and chronotropic effects in gastric muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Apical fluids were sampled at regular intervals after tissue mounting and extracellular LDH levels were measured using an enzyme assay kit (Sigma, Poole, Dorset, UK) adapted for isolated intestinal tissue enzyme release (32). The percent cytotoxicity was determined by comparing the amount of extracellular LDH observed in the apical chamber to the maximum releasable LDH induced by exposure to 0.01% Triton-X-100.…”
Section: Viability Of Ileal Mucosal Sheetsmentioning
confidence: 99%